2013
DOI: 10.3389/fncir.2013.00056
|View full text |Cite
|
Sign up to set email alerts
|

Medial cerebellar nuclear projections and activity patterns link cerebellar output to orofacial and respiratory behavior

Abstract: There is ample evidence that the cerebellum plays an important role in coordinating both respiratory and orofacial movements. However, the pathway by which the cerebellum engages brainstem substrates underlying these movements is not well understood. We used tract-tracing techniques in mice to show that neurons in the medial deep cerebellar nucleus (mDCN) project directly to these putative substrates. Injection of an anterograde tracer into the mDCN produced terminal labeling in the ventromedial medullary reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 48 publications
2
38
1
Order By: Relevance
“…Removal of the cerebellum results in slightly slower licking rates in rodents but does not appear to affect the generation of either rhythmic licking 98 or coordinated whisking and sniffing 18 . Together with observations that the deep cerebellar nuclei project to orofacial-related regions of the medullary reticular formation and spike in phase with licking 99 , these results may suggest that the cerebellum plays a role in modulating rather than patterning orofacial behaviors. Similarly, inputs from the basal ganglia have been shown to influence chewing and licking either directly or through the superior colliculus, or through both 100 .…”
Section: Regulation Of Orofacial Behaviors By Higher-order Brain Regionssupporting
confidence: 59%
See 1 more Smart Citation
“…Removal of the cerebellum results in slightly slower licking rates in rodents but does not appear to affect the generation of either rhythmic licking 98 or coordinated whisking and sniffing 18 . Together with observations that the deep cerebellar nuclei project to orofacial-related regions of the medullary reticular formation and spike in phase with licking 99 , these results may suggest that the cerebellum plays a role in modulating rather than patterning orofacial behaviors. Similarly, inputs from the basal ganglia have been shown to influence chewing and licking either directly or through the superior colliculus, or through both 100 .…”
Section: Regulation Of Orofacial Behaviors By Higher-order Brain Regionssupporting
confidence: 59%
“…Together the results suggest that control of rhythmic orofacial behaviors may involve the combination of a fast oscillatory drive signal controlled by a brainstem CRG, and slower amplitude and set-point modulation controlled by one or more independent mechanisms. These inputs may converge on brainstem motoneurons or on specific pre-motoneurons, such as those located outside the CPG, and those in superior colliculus 36, 63, 99, 112 .…”
Section: Regulation Of Orofacial Behaviors By Higher-order Brain Regionsmentioning
confidence: 99%
“…Chen and colleagues showed that the position of mystacial vibrissae in the mouse is represented in the simple spike activity of individual Purkinje cells in Crus I [123]. We reported representations of respiratory and whisker movements in the anterior vermis [124126]…”
Section: The Coordination Of Rhythmic Orofacial Movements: a Proposedmentioning
confidence: 99%
“…Such stereotypic, rhythmic movements are generally driven by separate brainstem central pattern generator circuits, some of which have more or less well-known locations in the brainstem (Travers et al, 1997;Feldman et al, 2003;Cramer et al, 2007). A recent anatomical study suggested that neurons in the medial cerebellar nuclei project directly to brainstem sites thought to contain those central pattern generator circuits (Lu et al, 2013). In vivo studies in rodents have shown that licking, breathing, and whisking are widely represented in Purkinje cell and CN spiking activity (Welsh et al, 1995;Hayar et al, 2006;Bosman et al, 2010;Bryant et al, 2010;Cao et al, 2012b;Lu et al, 2013).…”
Section: Coding Of Rhythmic Movements Through Common Rate Modulationmentioning
confidence: 99%
“…A recent anatomical study suggested that neurons in the medial cerebellar nuclei project directly to brainstem sites thought to contain those central pattern generator circuits (Lu et al, 2013). In vivo studies in rodents have shown that licking, breathing, and whisking are widely represented in Purkinje cell and CN spiking activity (Welsh et al, 1995;Hayar et al, 2006;Bosman et al, 2010;Bryant et al, 2010;Cao et al, 2012b;Lu et al, 2013). A role of the cerebellum in controlling or coordinating such rhythmic movements is further supported by studies in genetic mouse models of brain disorders involving cerebellar neuropathology, such as autism spectrum disorders.…”
Section: Coding Of Rhythmic Movements Through Common Rate Modulationmentioning
confidence: 99%